Development, fabrication and evaluation of a novel biomimetic human breast tissue derived breast implant surface. (February 2017) - Barr, S.; Hill, E.W.; Bayat, A.
Graphical abstract: Abstract: Breast implant use has tripled in the last decade with over 320, 000 breast implant based reconstructions and augmentations performed in the US per annum. Unfortunately a considerable number of women will experience capsular contracture, the irrepressible and disfiguring, tightening and hardening of the fibrous capsule that envelops the implant. Functionalising implant surfaces with biocompatible tissue-specific textures may improve in vivo performance. A novel biomimetic breast implant is presented here with anti-inflammatory in vitro abilities. Topographical assessment of native breast tissue facilitated the development of a statistical model of adipose tissue. 3D grayscale photolithography and ion etching were combined to successfully replicate a surface modelled upon the statistics of breast tissue. Pro-inflammatory genes ILβ1, TNFα, and IL6 were downregulated (p < 0.001) and anti-inflammatory gene IL-10 were upregulated on the novel surface. Pro-inflammatory cytokines Gro-Alpha, TNFα and neutrophil chemoattractant IL8 were produced in lower quantities and anti-inflammatory IL-10 in higher quantities in culture with the novel surface (p < 0.01). Immunocytochemistry and SEM demonstrated favourable fibroblast and macrophage responses to these novel surfaces. This study describes the first biomimetic breast tissue derived breast implant surface. Our findings attest to its potential translational ability to reduce the inflammatory phase of the implant driven foreign body reaction. Statement of Significance: Breast implants are still manufactured using outdated techniques and have changed little since their inception in the 1960's. Breast implants can cause a medical condition, capsular contracture which often results in disfigurement, pain, implant removal and further surgery. This condition is due to the body's reaction to these breast implants. This article describes the successful development and testing of a novel breast implant surface inspired by the native shapes present in breast tissue. Results show that this novel implant surface is capable of reducing the negative reaction of human cells to these surfaces which may help reduce capsular contracture formation. This work represents the first steps in producing a biocompatible breast implant.